Sex, environment, and death rate in a dementia cohort: a seven-years Bayesian survival analysis using medications data from a contaminated area in Italy - Mincuzzi, Antonia; Lodeserto, Paolo; Zollino, Jennifer; Sardone, Rodolfo; Bisceglia, Lucia; Addabbo, Francesco; Minerba, Sante; Colacicco, Vito Gregorio; Giannico, Orazio Valerio (Frontiers in Public Health, 2024)
Introduction: Studies have analyzed the effects of industrial installations on the environment and human health in Taranto, Southern Italy. Literature documented associations between different variables and dementia mortality among both women and men. The present study aims to investigate the associations between sex, environment, age, disease duration, pandemic years, antidementia drugs, and death rate. Methods: Data from the regional medication registry were used. All women and men with an antidementia medication between 2015 and 2021 were included and followed-up to 2021. Bayesian mixed effects logistic and Cox regression models with time varying exposures were fitted using integrated nested Laplace approximations and adjusting for patients and therapy characteristics. Results: A total of 7,961 person-years were observed. Variables associated with lower prevalence of acetylcholinesterase inhibitors (AChEIs) medication were male sex (OR 0.63, 95% CrI 0.42-0.96), age 70-79 (OR 0.17, 95% CrI 0.06-0.47) and ≥80 years (OR 0.08, 95% CrI 0.03-0.23), disease duration of 2-3 years (OR 0.43, 95%CrI 0.32-0.56) and 4-6 years (OR 0.21, 95% CrI 0.13-0.33), and pandemic years 2020 (OR 0.50, 95% CrI 0.37-0.67) and 2021 (OR 0.47, 95% CrI 0.33-0.65). Variables associated with higher mortality were male sex (HR 2.14, 95% CrI 1.75-2.62), residence in the contaminated site of national interest (SIN) (HR 1.25, 95% CrI 1.02-1.53), age ≥80 years (HR 6.06, 95% CrI 1.94-18.95), disease duration of 1 year (HR 1.50, 95% CrI 1.12-2.01), 2-3 years (HR 1.90, 95% CrI 1.45-2.48), 4-6 years (HR 2.21, 95% CrI 1.60.3.07), and pandemic years 2020 (HR 1.38, 95% CrI 1.06-1.80) and 2021 (HR 1.56, 95% CrI 1.21-2.02). Variables associated with lower mortality were medication of AChEIs alone (HR 0.69, 95% CrI 0.56-0.86) and in combination with memantine (HR 0.54, 95% CrI 0.37-0.81). Discussion: Male sex, age, disease duration, and pandemic years appeared to be associated with lower AChEIs medications. Male sex, residence in the SIN of Taranto, age, disease duration, and pandemic years seemed to be associated with an increased death rate, while AChEIs medication seemed to be associated with improved survival rate.